7+9=11(z-8)

Simple and best practice solution for 7+9=11(z-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+9=11(z-8) equation:


Simplifying
7 + 9 = 11(z + -8)

Combine like terms: 7 + 9 = 16
16 = 11(z + -8)

Reorder the terms:
16 = 11(-8 + z)
16 = (-8 * 11 + z * 11)
16 = (-88 + 11z)

Solving
16 = -88 + 11z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-11z' to each side of the equation.
16 + -11z = -88 + 11z + -11z

Combine like terms: 11z + -11z = 0
16 + -11z = -88 + 0
16 + -11z = -88

Add '-16' to each side of the equation.
16 + -16 + -11z = -88 + -16

Combine like terms: 16 + -16 = 0
0 + -11z = -88 + -16
-11z = -88 + -16

Combine like terms: -88 + -16 = -104
-11z = -104

Divide each side by '-11'.
z = 9.454545455

Simplifying
z = 9.454545455

See similar equations:

| 2x^2+17x-55=0 | | -16t^2+96t+80=124 | | 2/7m-1/3=4/5 | | 20+20+z=-20+5z | | -2y+16=4x | | -16t^2+96t+80=125 | | 28=3(2p-6) | | 7h(11h-8)= | | 3x(2x+20)=180 | | Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q |

Equations solver categories